A survey of health education in Grade six of Bulacan Province - Davis, Velma Lou 1922- ([Quezon City University of the Philippines], 1955)
The teaching of health education in the sixth grade in the classrooms of Bulacan Province was determined in this study. Since in most of the grade six classrooms, health is integrated into other subjects such as elementary science and social science, some information on the health curriculum can also be found in these courses of study.
Bibliography: l. 95-98.
Thesis (M.Ed.)--University of the Philippines, 1955
Vita.
Typewritten
Keywords: Health Education; Hygiene, Public -- Bulacan